Studi Pembuatan Minuman Instan Cangkang Telur Berkalsium Tinggi - Misril Fuadi; Wiri Arianingrum (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
A research on the manufacture of instant beverages high calcium eggshell calcium levels To Improve methods completely randomized design (CRD) with two (2) replicates. The first factor is the drying time (P) ie: P0 = 0 hours, P1 = 1 hour, P2 = 2 Hours, P3 = 3Jam. The second factor is the addition maltodekstrine (M) which consists of four levels, namely: M1 = 0.2%, M2 = 0.4% = 0.6% M3, and M4 = 0.8%. The parameters observed: Serum calcium, yield, TSS, water content, organoleptic aromas and flavors. The statistical analysis was obtained, that the drying time had highly significant effect (P <0.01) in the levels of calcium, TSS, water content, organoleptic aromas and flavors. Extra maltodektris provide highly significant effect (P <0.01) in the calcium, yield, TSS, and had no significant (P <0.05) against TSS.